PENGARUH CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK WARDAH DI GARUT KOTA - Nazwa Hidayat, Erika; Ramayani Yusuf (Universitas Haji Sumatera Utara, 2024)
PT Paragon Technology and Innovation, the largest cosmetics manufacturing company in Indonesia, makes Wardah, one of the beauty brands that was first launched to the public in 1995. In the fourth year, PT Paragon launched Wardah products. Wardah succeeded in obtaining Halal certification from LPOM MUI, making it a pioneer of Halal beauty product brands in Indonesia. The researcher's aim in conducting this research is to find out whether there is an influence between the